Evaluasi Penerapan Program KIP-Kuliah Mengacu Pada Pasal 76 UU No. 12 Tahun 2012 Menggunakan Metode Seven Tools di Teknik Industri Universitas Pamulang - Khairunnisa, Khairunnisa; Anedea, Tahta; Novianti, Irma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The KIP-Kuliah Scholarship is a government initiative to facilitate access to higher education, in line with the 1945 Constitution, which refers to Law No. 12 of 2012, particularly Article 31. This article regulates the rights and obligations of the citizens of the Republic of Indonesia, emphasizing the government's responsibility to pay special attention to the education sector in Indonesia. This study aims to identify factors influencing student achievement's degradation (decline) in meeting the mandatory and optional output targets. The research employs interview techniques using the Seven Tools method, a set of quality analysis tools proven effective in identifying, analyzing, and addressing issues faced by KIP-Kuliah scholarship recipients who have yet to fulfill the required outputs mandated by the government. The conclusion is that improvements are necessary to address challenges in the implementation of the KIP-Kuliah Program. It is essential to enhance student motivation and study habits to become more disciplined for student-related factors.